Respons Pertumbuhan Benih Tanaman Api-Api (Avicennia marina) Pada Berbagai Jenis Media Tanam - Elly Rosnarita; Rizani Rizani (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2021)
Api-api plant (Avicennia marina) is one type of plant found in mangrove forest vegetation. It grows in tidal areas with muddy, loam and sandy soil conditions. The growth and development of this plant is also influenced by the salinity of the water. To develop this plant, the obstacles faced in addition to its habitat which is in the tidal area which is strongly influenced by water salinity, also not much effort to cultivate this plant outside its habitat. The aim of this reasearch was to determine the response of the use of various kind of growth media such as soil, sea sand, river sand dan mixture of soil and sea sand to the growth of Api-api (Avicennia marina) seeds. The research was carried out using a Randomized Block Design (RBD) with 5 treatments and 5 replications consisting of 5 levels of growth media treatment. The data were analyzed by means of variance and to determine the mean value of the treatment, the Least Significant Difference (LSD) test was carried out at the 5% level. The results of this reasearch concluded that differences in growrth media had a higly significant effect on the growth of api-api seeds. Growth media that consist of mixed with soil and sea sand media and sea sand media showed better results in plant growth variables which include viability seed, number of leaves, plant height, stem diameter, root length, wet weight and dry weight of the plant.